Lost Stone During Laparoscopic Cholecystectomy: Retrieval Using a Condom. Issue 1 (1993) - Chung, S. C. S.; Li, M. K. W.; Li, A. K. C.
Abstract : Laparoscopic cholecystectomy is becoming increasingly popular for the treatment of gall stone disease. In this technique, the gall bladder is dissected free under laparoscopic vision and then extracted. We report an interesting complication that occurred during extraction of a gall bladder containing a large stone and a novel method of overcoming the problem.